A Study on Numerical Simulation to Analyze the Behavior of Reinforced Concrete Technical Manholes - Dao, SyDan (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2025)
With the rapid development of infrastructure, technical manholes play a crucial role in the construction of drainage systems and utility conduits. This paper presents a numerical simulation method for analyzing the behavior of reinforced concrete technical manholes on highways in Vietnam using Plaxis 3D software. The study focuses on large, cast-in-place technical manholes, which are subjected to complex loading conditions, including surrounding soil pressure, water pressure, and live loads from vehicles. The results demonstrate that the primary internal force components (bending moments and shear forces) can be accurately determined, providing a foundation for verifying or designing reinforced concrete manholes in highway projects in Vietnam. The results for bending moments and shear forces calculated using the approximate method are overly conservative; they are about 1.4 times greater than the results obtained from the numerical method. This method offers valuable insights for optimizing the design process, reducing material costs, and providing a more precise approach compared to traditional manual calculations. The findings contribute to improving the design and construction of reinforced concrete technical manholes in Vietnam’s highway infrastructure.